The next frontier in osseointegration: energy and speed as critical determinants and their enhancement by UV photofunctionalization - Takanori Matsuura; Keiji Komatsu; Rune Shibata; Toshikatsu Suzumura; Justin Choi; Takahiro Ogawa (International Journal of Implant Dentistry)
Abstract Purpose This study aimed to redefine biomechanical understanding of osseointegration by dissecting its multi-faceted nature—strength, stiffness, energy, and the speed of development—through in vivo analysis Methods Titanium implants were placed bilaterally in rat femurs, with one side receiving ultraviolet (UV) photofunctionalization and the contralateral side serving as untreated control. Biomechanical push-in tests were performed at day 4, and weeks 1 to 3 post-implantation. Yield strength, elastic modulus, toughness, and energy were measured over time, and their rates of change were calculated to assess dynamic progression. Mineralization at the bone–implant interface was quantified using energy-dispersive X-ray spectroscopy. Results Yield strength followed a second-degree growth curve, plateauing over time in control implants. Derivative analysis revealed that the speed of strength gain peaked early and then declined. In contrast, osseointegration energy steadily increased throughout healing, with its rate of gain accelerating over time. Yield strength correlated quadratically with peri-implant mineralized tissue, indicating early saturation, while energy and toughness showed a continuous linear relationship. UV photofunctionalization enhanced all biomechanical parameters. Notably, it accelerated early strength acquisition (up to 3-fold) and markedly increased both energy (up to 3.4-fold) and its rate of development (up to 4.9-fold). Conclusions By introducing energy and its speed as novel indices, this study offers a more dynamic and functionally relevant framework for evaluating osseointegration. UV photofunctionalization not only accelerates early mechanical stability but amplifies energy acquisition at the bone–implant interface, promoting faster and more robust development of mechanical resilience. Graphical Abstract